Wildlife tourism, environmental learning and ethical encounters : ecological and conservation aspects / [Editor] Ismar Borges de Lima; Ronda Green - Green, Rondaeditor
This book outlines the status quo of worldwide wildlife tourism and its impacts on planning, management, knowledge, awareness, behaviour and attitudes related to wildlife encounters. It sets out to fill the considerable gaps in our knowledge on wildlife tourism, applied ecology, and environmental education, providing comprehensive information on and an interdisciplinary approach to effective management in wildlife tourism. Examining the intricacies, challenges, and lessons learned in a meaningful and rewarding tourism niche, this interdisciplinary book comprehensively examines the major potentials and controversies in the wildlife tourism industry. Pursuing an insightful, provocative and hands-on approach, it primarily addresses two questions: 'Can we reconcile the needs of the wildlife tourism industry, biodiversity conservation, ecological learning and animal ethics issues?' and 'What is the Future of the Wildlife Tourism Industry?'. Though primarily intended as a research text, it also offers a valuable resource for a broad readership, which includes university and training students, researchers, scholars, tourism practitioners and professionals, planners and managers, as well as the staff of government agencies.